Increasing Red Onions (Allium ascalonicum L.) Growth and Yield by Providing Goat Urine LOF Concentration and Paclobutrazol Retardant - Wanda Mudhalifah; Didik Utomo Pribadi; Sukendah (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2025)
Shallots (Allium ascalonicum L.) are an economically important horticultural crop that contributes to national consumption, farmer income, and foreign exchange earnings. This study aimed to determine the optimal concentrations of goat urine liquid organic fertilizer (LOF) and the plant growth regulator (PGR) paclobutrazol for enhancing shallot growth and yield. The experiment was conducted using a factorial arrangement in a Split-Plot Design with two factors and three replications. The main plot consisted of four levels of goat urine LOF (0, 100, 150, and 200 mL/L), while the subplot consisted of four levels of paclobutrazol (0, 100, 250, and 300 ppm). The results showed significant interactions between goat urine LOF and paclobutrazol on leaf and tiller numbers. Application of goat urine LOF at 100 mL/L produced the largest bulb diameter, whereas the absence of paclobutrazol (0 ppm) resulted in the greatest plant height. These findings indicate that moderate concentrations of goat urine LOF, combined with limited or no paclobutrazol application, can optimize shallot growth and yield.